Openness and Agricultural Performance in Ghana (Journal of Science and Technology, 2016)
The paper examined the relationship between openness and agricultural performance using data covering the period 1995 to 2009. Representing openness as foreign direct investment (FDI) and trade openness, the results showed that there is no long run relationship between FDI and trade openness on one hand and agricultural performance on the other. In the short run, vtrade openness and FDI exerted a statistically significant negative effect on agricultural performance. Though inelastic, the sign of the coefficients showed that increased openness of Ghana’s agriculture through trade and FDI do not promote performance of the sector. These results provide evidence for an examination of the type of FDI attracted into the sector. Also, the detrimental effect of trade openness suggests a re-examination of the free trade policy to provide some cushion to sections of the sector to enhance output thereby increasing performance.